Novel Watermarking Methods Based on Frequency Domain and Singular Value Decomposition - Cika, Petr; Zukal, Martin (Communications - Scientific letters of the University of Zilina, 2013)
Nowadays, the copyright laws protecting the digital content are getting quite common. One of the important things is to protect the original or compressed images against illegal use. Frequency domain watermarking methods are used in most cases in today’s image- and videowatermarking algorithms. Especially Discrete Wavelet Transform (DWT) and Discrete Cosine Transform (DCT) are used in watermarking algorithms. This paper deals with development of two novel digital image watermarking methods that use DWT with Singular Value Decomposition (SVD) and DCT with SVD. The paper includes step by step process of watermark embedding and extraction and testing of the watermark robustness. The robustness was tested with the Checkmark, one of the watermark benchmarking tools. Experimental results show that both schemes are robust against a lot of attacks and have very high data hiding capacity.